The house of Hades - Riordan, Rick (New York : Disney-Hyperion Books, 2013)
"Greek and Roman demigods from the Prophecy of Seven must work together to seal the Doors of Death--and help Percy and Annabeth escape the Underworld in the process"--
Keywords: Mythology, Roman -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Giants -- Juvenile fiction; Camps -- Juvenile fiction; Hera (Greek deity) -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction; Fantasy fiction